Microwave barrel reactor use in trimethylolpropane oleate synthesis by Candida antarctica lipase in a biphasic non-solvent process - Happe, Manuel; Grand, Pascal; Farquet, Sébastien; Aeby, Sandrine; Héritier, Jean-Claude; Corthay, François; Mabillard, Eric; Marti, Roger; Vanoli, Ennio; Grogg, Alain-François; Nussbaum, Samuel; Roduit, Alain; et al. (Green chemistry : an international journal and green chemistry resource : GC, 2012)
A novel microwave barrel reactor (MBR) was constructed and used in lipase catalyzed biolubricant synthesis. The MBR is thought as a versatile process tool for biotransformation and green chemistry that overcomes current size limitations in microwave reactors. A lipase mediated biotransformation in the MBR was compared to a state of the art jacketed reactor with external heat exchanger. Oleic acid and trimethylolpropane converted quantitatively (96%) into biolubricants using microwave induction. The heat dissipation in the MBR was analyzed by thermal imaging and inside thermometry. Conversion rates, rate constants and pseudo reaction orders were in line with conventional processing and no microwave effect was detected. The MBR is a versatile new reactor for non solvent, minimal and common solvent processing in the microwave field. While the subject of investigations was biolubricant synthesis in the MBR, the technology described is of wider potential interest in the field of biomass processing and sustainable chemical manufacture.